Need for Entrepreneurial Orientation from The Perspective of Different Organizational Levels - Agnieszka FILIPOWICZ; Małgorzata OKRĘGLICKA (Communications of International Proceedings, 2020)
The entrepreneurial orientation is a very important construct to assure the proper functioning of an organization. For the purpose of this article, a five-dimensional concept of the entrepreneurial orientation has been adopted. This article aims to identify the challenges and threats that must be faced by individuals within an organization, depending on their position in the hierarchy. In order to collect some necessary data we conducted interviews with employees representing various levels in the chosen organization. The data reveal that the perception of the entrepreneurial orientation differs depending on the held position. Based on the collected figures, we formulated an additional conclusion of how important it may be for all employees to stay informed and acknowledge the adopted strategy, regardless their position within the company. When being properly informed and thus entirely aware of the implemented strategy, employees are prone to entrepreneurial activities.
Keywords: Entrepreneurial Orientation; Organizational Culture; Organizational Level